The profile of the dermatoses in children with the HIV virus at the Fundação de Medicina Tropical do Amazonas Perfil das dermatoses em crianças portadoras do vírus HIV na Fundação de Medicina Tropical do Amazonas - Eleonora Dantas Dias; Maria da Graça Souza Cunha; Sinésio Talhari (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: The Acquired Immunodeficiency Syndrome (AIDS) constitutes a sub-epidemic in Brazil. Due to the increasing number of women infected by the virus, the vertical transmission increased substantially, and due to the lack of adequate prophylactic treatment, many children are infected and show manifestations of the disease in early ages. Multiple systems are affected by the HIV virus, and the skin is often the first organ to be involved. OBJECTIVES: The objective of this study is to analyze the clinic, dermatological and epidemiological profiles of children carriers of the virus in the City of Manaus aiming at identifying the most frequent dermatoses that affect these children and try to relate these dermatoses to the immunologic deterioration. METHODS: A study was conducted where children carriers of the HIV virus from the Fundação Alfredo da Matta and Fundação de Medicina Tropical were studied from March 2007 to July 2008. These children were submitted to dermatological and laboratorial exams such as viral load dosage and CD4+ and CD8+ counts. RESULTS: During the study period, 70 HIV + children were examined; all of them had AIDS and had been contaminated by vertical transmission. The average number of dermatoses by children was 1.73, and 95.5% had at least one dermatosis during the study period. The most frequent manifestations were atopic dermatitis (22.9%), childhood prurigo (20%) and warts (18,6%). CONCLUSIONS: Children with HIV/AIDS have more skin disorders than children without HIV/AIDS. There was no statistical difference between the children in the group using ARVT and the group that wasn't using it. FUNDAMENTOS: A Síndrome da Imunodeficiência Adquirida (AIDS) tem se configurado como uma sub-epidemia no Brasil, devido ao crescente número de mulheres infectadas pelo vírus, a transmissão vertical aumentou significativamente, e devido à falta de tratamento profilático adequado, muitas crianças são infectadas e convivem com as manifestações da doença precocemente. Múltiplos são os sistemas acometidos pelo vírus HIV, sendo a pele muitas vezes o primeiro órgão acometido. OBJETIVOS: O estudo teve por objetivo analisar o perfil clínico-dermatológico e imunológico das crianças portadoras do vírus HIV na cidade de Manaus com a finalidade de identificar as dermatoses mais freqüentes que as acometem e relacioná-las com a deterioração de seu sistema imunológico. MÉTODOS: Realizou-se um estudo onde foram acompanhadas entre março de 2007 a julho de 2008, crianças portadoras do vírus HIV atendidas na Fundação de Medicina Tropical do Amazonas. Estas foram submetidas a exame dermatológico e a exames laboratoriais como dosagem de carga viral, CD4+, CD8+. RESULTADOS: Durante o período estudado, foram atendidas 70 crianças HIV+, todas já apresentavam AIDS e tinham sido contaminadas por transmissão vertical. A média de dermatose por criança foi de 1,73 sendo que 95,5% apresentaram pelo menos uma dermatose. As manifestações mais freqüentes foram: dermatite atópica (22,9%), prurigo estrófulo (20%) e verruga (18,6%). CONCLUSÃO: As crianças com HIV/AIDS apresentaram mais dermatoses do que as crianças sem HIV/AIDS. Não houve diferença estatística em relação às dermatoses entre o grupo de crianças que estava em uso de Terapia antiretroviral (TARV) e o que não estava.